1992
DOI: 10.1093/jmedent/29.4.577
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Transmission by Anopheles subpictus (Diptera: Culicidae) in a New Irrigation Project in Sri Lanka

Abstract: Indoor resting Anopheles subpictus in a new irrigation scheme in Sri Lanka were investigated during 1989-1990 for malaria infection by dissection and ELISA, and human feeding rates by ELISA analysis of blood meals. Indoor resting abundance was 22.3 females per house per 15-min catch in April-June 1989, 2.2 in November-December 1989, and 7.5 in April-June 1990. ELISA-based malaria infection rates (Plasmodium vivax and P. falciparum combined) were 1.4% during April-June and 3.2% during November-December 1989, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Serologic evidence for VK247 infection in humans in Sri Lanka has also been reported. 21 It is evident that previous ELISA studies [4][5][6][7][8] that used only the PV-210 polymorph would have underestimated the CS protein rates of P. vivax in Sri Lankan anophelines and thereby the VC and EIR estimates based on these rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Serologic evidence for VK247 infection in humans in Sri Lanka has also been reported. 21 It is evident that previous ELISA studies [4][5][6][7][8] that used only the PV-210 polymorph would have underestimated the CS protein rates of P. vivax in Sri Lankan anophelines and thereby the VC and EIR estimates based on these rates.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the methodologies used have been published previously. 4,5,12 Both HBC and CBC were restricted to the first half of the night due to hazards associated with the study area being located close to a civil war zone within Sri Lanka. However, this limitation would not have significantly biased anopheline catches, since previous studies in Sri Lanka have shown that 65-85% of the host-seeking females of the species collected herein bite before midnight.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By increasing surface water levels, irrigation modifies ecohydrological conditions of the landscape, creating more standing bodies of water for longer periods of time (5), thereby increasing the abundance of mosquito breeding sites and adult vector populations (6)(7)(8)(9)(10)(11)(12)(13). In addition, agricultural development can increase the frequency of human-vector contact, when human labor and mosquito breeding seasons are synchronized (14), and promotes migration to newly irrigated areas (15), thus changing the spatial scale of malaria transmission.…”
mentioning
confidence: 99%